PENGARUH JARAK STRAW DENGAN NITROGEN CAIR PADA PROSES PRE FREEZING TERHADAP KUALITAS SEMEN BEKU SAPI LIMOUSIN - Aini, Kurotul; Suharyati, Sri; Hartono, Madi (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
This study aimed to determine the effect of straw space with liquid nitrogen on pre freezingprocess and the best straw space to the quality of frozen semen of Limousin Cows so that they areappropriate for Artificial Insemination process. This study was conducted in Regional TechnicalService Unit-Regional Artificial Insemination Office Lampung, Terbanggi Besar District, CentralLampung Regency, Lampung Province on 7th—13 th April 2014. The Completely RandomizedDesign (CRD) was used is these research with five treatments of straw spaces, 2 cm, 4 cm, 6 cm, 8cm, and 10 cm, with 4 replications. The data obtained was analyzed by using variance analysisandcontinued by Polinomial Ortogonal test.The result of this study showed that the straw space was significantly (P<0,01) to the motilityand live spermatozoa after thawing. However it was not significantly (P>0,05) to the motility and livespermatozoa after pre freezing. Polinomial Ortogonal test, obtained that the straw space wassignificantly (P<0,01) to the motility and live spermatozoa after thawing, had quadratic pattern withequation of Y = - 6,50 + 12,09x – 0,89x2 ; R2 = 41,3%, with the best effect on the straw space of 6 cm,that is 34%. Besides, the straw space was also different (P<0,01) to percentage of live spermatozoaafter thawing, had quadratic pattern with equation of Y = 8,97 + 8,81x - 0,64x2 ; R2 = 41,3%, withthe best effect on the straw space of 6 cm, that is 38,79%.